The Employees Perception Analysis toward The Operational Expectation and Reality based on Ishikawa and Spider Plot Methods at PT. Tata Makmur Bersama – Sidoarjo ,Indonesia - Wanda Gema P.A Hidayat (Program Studi Agribisnis, 2023)
The purpose of this study is to examine and analyze the employees’ perception toward the operational expectation and reality in the production factors based on Ishikawa and Spider Plot at PT. Tata Makmur Bersama – Sidoarjo. The population of this study is all 198 employees of PT. Tata Makmur Bersama - Sidoarjo, and the sample technique is saturated sampling, where the sample is the whole population. This study finds that the employees’ perception and expectation toward the operational reality can be identified as good category, through the average of Customer Satisfaction Index (CSI) in all aspects analysis. Nevertheless, only few production aspects that the firm is doing well; consequently the employees feel receiving inadequate treatments. This study enlightens the distinction of the Improvement Ratio (IR) as scale through Cartesian and Spider Plot diagrams due to the ability to reveal the broaden deviation between the operational expectation and reality that cause employees’ tremendous dissatisfaction. In addition, this study presents the short-term priority scale to enhance the primary priority quadrant in order to explain the short-term and long-term management’s strategy map that shows in Cartesian diagram. Furthermore, this study recommends the firm’s management could utilize the data at Achievement Maintenance Quadrant and Low Priority to improve the long-term management’s strategy map. Keywords: Employees’ Perception; Expectation and Actuality; Ishikawa Method; Spider Plot; Priority Scale